Problem-Based Learning on the Abilities of Writing Argumentation Communications of Malay-Indonesia Department Students - Agus Sulaeman (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
The aim of this research is to determine the effect of the problem-based learning model on the ability to write argumentative essays of Malay-Indonesian study program students in the 4th semester audio visual course. In this research, this research used a quasi-experimental method by conducting a pre-test and post-test in two groups. This type of experimental research method uses a nonequivalent control group design, where the experimental class is treated and the control class is not treated. This nonequivalent control group design is almost the same as the pretest and posttest control group design, only in this design the experimental and control groups are not chosen randomly. Data collection techniques use tests. Data analysis techniques start from the normality test, homogeneity test, and continue with hypothesis testing.research data,So that post-test or final test data was obtained which was then analyzed using a two-sided T test, giving results that students who were given problem-based learning model learning treatment experienced more improvement compared to students who were not given problem-based learning strategies. This means that it is in accordance with the proposed hypothesis and it can be concluded that there is a difference in the ability to write argumentative essays between students who are given a problem-based learning model and students who are not given a problem-based learning model.